Afrofuturism and the case of Black Panther (2018) = Thuyết vị lai châu Phi và câu chuyện về Black Panther (2018) - Vũ, Phương Thảo (2021)
This paper is a humanities-oriented research that investigates the development of a cultural aesthetic named Afrofuturism and examines the blockbuster superhero movie Black Panther as an artistic form that contributes to the development and widespread of the phenomenon. In the first part, this paper offers informative knowledge about the history of Afrofuturism, presenting how the shape of the phenomenon changed over time thanks to the active movements of Afrofuturists. This is achieved by analyzing the characteristics of the ideology in different points throughout history, from the middle of the 20th century to the arrival of the Black Panther, and identifying the related relating representative contributors. In the latter part, the case – Black Panther – is evaluated by comparing and contrasting its features with that of Afrofuturism during the same period. The results of this study are that Black Panther features all characteristics of Afrofuturism of the period the movie was born. Besides, the film also adds one component of the cultural aspect of the phenomenon that has not been observed in any prior works of the 21st century – the Xhosa African language as a national and dominant language. Finally, there are some suggestions regarding the possible future research approaches of the same topic – Afrofuturism and Black Panther